Carbon nanotube hybrid nanostructures: future generation conducting materials. Issue 24 (2nd June 2016) - Chinnappan, Amutha; Baskar, Chinnappan; Kim, Hern; Ramakrishna, Seeram
Abstract : CNT based nanocomposites are very attractive and an emerging new class of materials with unique properties. They are a major part of nanotechnology and capable of developing several fields in materials science and engineering. Abstract : The present electronic age has seen rapid advancements in the performance and versatility of electronic devices along with a simultaneous decrease in their dimensions. Miniaturising electronic devices increases their portability and ease of handling, making them ubiquitous in the modern world. Likely developments awaiting the science and technology of next-generation conducting materials are based on CNT hybrid nanomaterials. In recent times, carbon nanotubes based hybrid nanomaterials have attracted significant attention due to their unique electronic, optical, thermal, mechanical, and chemical properties. CNT powders are incorporated in diverse commercial products ranging from rechargeable batteries, automotive parts, and sporting goods to boat hulls and many more. In this review we focus on CNT based nanocomposite materials and their applications.